Molecular characterization using simple sequence repeat (SSR) markers points to population admixture of genetic variation among introduced cashew (Anacardium occidentale L.) in northern Cameroon - Arlette Zaiya Zazou; Liliane Iyale; Joël Romaric Nguepdjop; Sobda Gonne; Sali Bourou; Oumarou Palou Madi; Sawil Ba-Ada; Daniel Daawe Manhouli; Yvonne Djeoufo; Merline Yoyo Fankou Dougoua; Pape Ibrahima Djighaly; Saliou Fall (Genetic Resources and Crop Evolution, 2026)

Pollution assessment around a big city in West Africa reveals high concentrations of microplastics and microbiologic contamination - Amidou Sonko; Patrice Brehmer; Guillaume Constantin de Magny; Gaël Le Pennec; Bissoume Sambe Ba; Ousmane Diankha; Mamadou Fall; Isabelle Linossier; Maryvonne Henry; Issa N’Diaye; Saliou Faye; Yoba Kande; et al. (Regional Studies in Marine Science, 2023)

Assessment of the global toxicity of marine sediments from the Dakar peninsula (Senegal, West Africa) - Amidou Sonko; Dalyal Copin; Patrice Brehmer; Cheikh Diop; Guillaume Constantin De Magny; Mamadou Fall; Yoba Kande; Patricia Moulin; Naby Souleymane Faye; Saliou Faye; Isabelle Linossier; Gaël Le Pennec (Environmental Monitoring and Assessment, 2023)

Methanogenic and fertilizing potential of aquaculture waste: towards freshwater farms energy self‐sufficiency in the framework of blue growth - Ndeye Aida Ndiaye; Halima Maiguizo-Diagne; Hamet Diaw Diadhiou; Waly Ndianco Ndiaye; Fulgence Diedhiou; Laurent Cournac; Mohamed Lamine Gaye; Saliou Fall; Patrice Brehmer (Reviews in Aquaculture, 2020)
The fisheries sector, particularly aquaculture, is a fundamental source of nutrition for humans, particularly in developing countries. The modern development of fish farming requires energy for production systems. This study investigates the potential of using organic wastes derived from fish fattening to produce on‐farm energy through the process of methanization. Oreochromis niloticus faeces methanogen potential was determined with (IFF) and without (UIFF) methanizer microbial inoculum. At the end of the manure methanation trials, the resulting digestates were tested as organic fertilizers for agriculture. The tests showed that inoculated fish faeces had faster biogas kinetics production compared with uninoculated fish faeces. In both cases, the produced biogas contained more than 60% methane (CH 4 ) from the second week of incubation, indicating that it was of good quality. Furthermore, the total CH 4 volume was twice as larger in IFF compared with UIFF. Biofertilizer tests showed no significant differences for most of the growth parameters in onion and tomato when compared to the unfertilized control, except in one case for tomato plants, which significantly increased its aboveground biomass. The results show that fish faeces are good methanogenic substrates conducive to energy recovery that could facilitate farm autonomy; however, valorization of the digestates as biofertilizer still requires extensive agronomic optimization. Based on our results, we estimate that equivalents of energy need of almost ten millions of people could be covered using the aquaculture potential in freshwater fish faeces biogas worldwide or that at least aquaculture farm energy self‐sufficiency could be fostered.

Effect of Eucalyptus camaldulensis amendment on soil chemical properties, enzymatic activity, Acacia species growth and roots symbioses - Abdoulaye Soumare; Anicet Manga; Saliou Fall; Mohamed Hafidi; Ibrahima Ndoye; Robin Duponnois (Agroforestry Systems, 2015)

Variation in the distribution of monosaccharides in soil fractions in the mounds of termites with different feeding habits (Senegal) - Saïdou Sall; Alain Brauman; Saliou Fall; Corinne Rouland; Edouard Miambi; Jean-Luc Chotte (Biology and Fertility of Soils, 2002)